PENINGKATAN UPAYA PENCEGAHAN PENYEBARAN COVID-19 SERTA PROMOSI KESEHATAN DI CLUSTER JADE BEKASI - Leonov Rianto; Aries Meryta; Doni Iswandani; Alifa Sabrina (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
The first two cases of COVID-19 in Indonesia were confirmed for the first time on March 2, 2020. Transmission occurred very quickly, on December 3, 2020 there were 8,369 positive cases of COVID-19. A study shows that the rate of transmission from contact with 1 patient can infect 3 people around him and maybe more. In minimizing the spread of the virus, the Government has launched a Health Protocol that applies throughout Indonesia. The details in the Health protocol need to be socialized more regularly, such as what type of mask should be used, how to use a mask correctly, how to wash hands properly, what is the safe distance between humans in public spaces, and so on. So, we intend to hold educational activities about preventing the spread of COVID-19 and promoting health in implementing health protocols. Based on statistical tests, it is known that the significance value (sig) of the pretest and posttest data is 0.000, which means that the H1 hypothesis is accepted because sig < 0.005. Hypothesis H1 is accepted, which means that there is an effect of counseling in increasing knowledge of health protocols. The highest increase in respondents' knowledge is in the section on how to wash hands properly.